2022
DOI: 10.3390/mi13071084
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Laser Processing Technology for Anti-Reflection Surfaces of Hard Materials

Abstract: The anti-reflection properties of hard material surfaces are of great significance in the fields of infrared imaging, optoelectronic devices, and aerospace. Femtosecond laser processing has drawn a lot of attentions in the field of optics as an innovative, efficient, and green micro-nano processing method. The anti-reflection surface prepared on hard materials by femtosecond laser processing technology has good anti-reflection properties under a broad spectrum with all angles, effectively suppresses reflection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 143 publications
0
5
0
Order By: Relevance
“…The anti-re ective properties of material surfaces can improve the resolution of speci c electromagnetic signals and aid in the shielding and elimination of clear interference signals [25]. Metal surfaces with both superhydrophobicity and anti-re ection have broad applications in elds such as solar cells, optoelectronic products, and military stealth.…”
Section: Anti-re Ective Propertiesmentioning
confidence: 99%
“…The anti-re ective properties of material surfaces can improve the resolution of speci c electromagnetic signals and aid in the shielding and elimination of clear interference signals [25]. Metal surfaces with both superhydrophobicity and anti-re ection have broad applications in elds such as solar cells, optoelectronic products, and military stealth.…”
Section: Anti-re Ective Propertiesmentioning
confidence: 99%
“…Undesired reflected light can lead to a reduction in optical power and the lifespan of these devices. [ 24 ] Prior to the discovery of structured anti‐reflective surfaces in nature, anti‐reflective coatings were primarily employed to diminish surface reflectivity. Various strategies were developed for this purpose, as described below.…”
Section: The Physics Behind Optical Multifunctional Surfacesmentioning
confidence: 99%
“…In nature, dragonflies are famous for not only their wonderful flying skills but also their excellent antireflectivity and superhydrophobicity due to the special structures on their wings. Dragonfly provides great inspiration for the fabrication of anti-reflective surfaces with microstructures array. It has been demonstrated that the manufacture of biomimetic anti-reflective subwavelength structure (ASS) array on the surface of infrared windows can provide a gradient refractive index profile between the two sides of the interface, which can significantly improve transmittance and hydrophobic properties. …”
Section: Introductionmentioning
confidence: 99%